DARI FILANTROPI KE ARSITEKTUR NILAI: INTEGRASI EMBEDDED ESG DALAM EKOSISTEM PEMBIAYAAN INKLUSIF PUSAT INVESTASI PEMERINTAH SEBAGAI INSTRUMEN KETAHANAN PANGAN ASTA CITA - Ismed Saputra; Mohamad Rizan; Muhammad Awaluddin (Bajang Institute, 2026)
This article examines the paradigmatic transformation of the Government Investment Center (PIP) from a conventional ultra-micro financing institution to one that organically integrates Environmental, Social, and Governance (ESG) principles into its core business processes. Unlike conventional CSR approaches that remain peripheral to business operations, Embedded ESG positions sustainability as an endogenous variable inseparable from capital allocation decisions and institutional design. Leveraging the regulatory expansion under PMK No. 130/2024, PIP now reaches Non-Financial Services Institutions (Non-LJK) including commodity aggregators, agribusiness off-takers, and digital agricultural platforms opening financing access for agricultural, plantation, and livestock communities suffering from financial exclusion due to market failure (Stiglitz & Weiss, 1981), while building a closed-loop ecosystem with effective interest rates below 4% per annum. The article analyzes the PT ALKO Sumatera Kopi case as a prototype Non-LJK ecosystem and formulates The Embedded ESG – Inclusive Micro Financing Framework (EE-IMFF), arguing that ESG is not a compliance burden but a genuine value creation engine for Indonesia's Asta Cita food security agenda.